2000
DOI: 10.4049/jimmunol.165.8.4624
|View full text |Cite
|
Sign up to set email alerts
|

CD47 Ligation Selectively Inhibits the Development of Human Naive T Cells into Th1 Effectors

Abstract: The CD47 Ag, also named integrin-associated protein, was recently reported to regulate the production of IL-12 by human monocytes and dendritic cells. The present study shows that CD47 ligation by CD47 mAb in primary cultures of cord blood mononuclear cells inhibits IL-12-driven Th1 cell development, as revealed by the cytokine secretion profile at restimulation and IFN-γ production at the single-cell level. F(ab′)2 fragments of CD47 mAb or the synthetic peptide 4N1K, corresponding to the CD47 binding site of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
59
0

Year Published

2001
2001
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 77 publications
(63 citation statements)
references
References 62 publications
(49 reference statements)
3
59
0
Order By: Relevance
“…Ligation of CD47 by a soluble mAb reportedly inhibited IL-12 responsiveness by PHA-activated neonatal mononuclear cells (11). In the course of this study, we confirmed and extended these observations to activated adult PBMC.…”
Section: Cd47 Ligation Down-regulates Il-12 Responsivenesssupporting
confidence: 78%
See 1 more Smart Citation
“…Ligation of CD47 by a soluble mAb reportedly inhibited IL-12 responsiveness by PHA-activated neonatal mononuclear cells (11). In the course of this study, we confirmed and extended these observations to activated adult PBMC.…”
Section: Cd47 Ligation Down-regulates Il-12 Responsivenesssupporting
confidence: 78%
“…When immobilized, CD47 mAb costimulated IL-2 production by CD3-activated normal or transformed adult T cells (17,18), whereas, in soluble form, it inhibited allogeneic MLR (19). It also decreased IL-2 production and IL-12R␤2 expression by IL-12-and PHAactivated naive cells; the latter is completely restored by addition of exogenous IL-2 at priming (11). Similarly, IL-2 abrogated the CD47 mAb-mediated inhibition of IL-12 responsiveness in anti-CD3-activated adult T cells (M. Sarfati, data not shown).…”
Section: Discussionmentioning
confidence: 88%
“…By contrast, the soluble SIRP␣1-Fc fusion protein, which efficiently bound CD47 (results not shown), had no apoptotic effect, regardless of the amount of protein or the incubation time we used. It is worth noting that only high concentrations of 4N1K (400 M) are able to induce cell death, whereas lower concentrations have been reported to sustain clonal expansion of inflammatory T cells (39) or to induce anergy of naive T cells (40,41). This apoptotic effect of 4N1K on T cells is not due to a nonspecific cytotoxicity, because CD47-deficient cells are resistant to cell death induced by 4N1K.…”
Section: Fig 2 Cd47 Interacts With the Bh3-only Protein Bnip3mentioning
confidence: 99%
“…CD47 may also function as a costimulator to regulate T cell activation, survival, and Th1 versus Th2 differentiation (4,5). Endogenous ligands for the extracellular domain of CD47 include the secreted protein thrombospondin-1 (TSP1) 1 and potentially other members of the thrombospondin family, several integrins (6 -9), and some members of the signal-regulatory protein family (3, 10 -13).…”
mentioning
confidence: 99%